2014
DOI: 10.1038/ncomms4750
|View full text |Cite
|
Sign up to set email alerts
|

KCNE1 divides the voltage sensor movement in KCNQ1/KCNE1 channels into two steps

Abstract: The functional properties of KCNQ1 channels are highly dependent on associated KCNE β subunits. Mutations in KCNQ1 or KCNE subunits can cause congenital channelopathies, such as deafness, cardiac arrhythmias, and epilepsy. The mechanism by which KCNE1 beta subunits slow the kinetics of KCNQ1 channels is a matter of current controversy. Here we show that KCNQ1/KCNE1 channel activation occurs in two steps: first, mutually independent voltage sensor movements in the four KCNQ1 subunits generate the main gating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
140
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(167 citation statements)
references
References 33 publications
22
140
0
5
Order By: Relevance
“…On the other hand, as previously reported 34 , WT with KCNE1 showed a large fluorescence change at hyperpolarized potentials far below the threshold of the ionic current ( À 40 mV) and did not saturate either end of the voltage (between À 160 and þ 80 mV). The F-V relationship obviously has two components; the first and leftshifted component relative to G-V curve and the 2nd component activating at depolarized potential and seemingly related to channel opening (G-V relationship) as previously reported by Osteen et al 34 , and as very recently clearly shown by Barro-Soria et al 41 F-V relationships of F232A þ KCNE1 and F279A þ KCNE1 are basically similar to that of WT, having the two fluorescent components. However, the second components are larger in the Phe mutants, especially in F279A þ KCNE1, probably due to the left-shifted G-V curves in the mutants if the second component actually tracks the channel opening as suggested 34 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, as previously reported 34 , WT with KCNE1 showed a large fluorescence change at hyperpolarized potentials far below the threshold of the ionic current ( À 40 mV) and did not saturate either end of the voltage (between À 160 and þ 80 mV). The F-V relationship obviously has two components; the first and leftshifted component relative to G-V curve and the 2nd component activating at depolarized potential and seemingly related to channel opening (G-V relationship) as previously reported by Osteen et al 34 , and as very recently clearly shown by Barro-Soria et al 41 F-V relationships of F232A þ KCNE1 and F279A þ KCNE1 are basically similar to that of WT, having the two fluorescent components. However, the second components are larger in the Phe mutants, especially in F279A þ KCNE1, probably due to the left-shifted G-V curves in the mutants if the second component actually tracks the channel opening as suggested 34 .…”
Section: Resultssupporting
confidence: 80%
“…Therefore, to keep the open state of WT KCNQ1/KCNE1 channel, higher depolarization is required. This final transition from the pre-upstate to the upstate may correspond to the second voltage sensor movement proposed by Barro-Soria 41 , which is seen as the second fluorescent component in Fig. 4a,b.…”
Section: Discussionsupporting
confidence: 57%
“…5 A and B) to determine whether the effects of KCNE3-FTL on voltage sensor movement and gate opening resemble the effects of KCNE3 or KCNE1. Similar to the F(V) of KCNQ1/KCNE1 channels (29) (Fig. 5B, dashed red line), the F(V) relation in KCNQ1/KCNE3-FTL channels comprises two components, with a first, major fluorescence component at more negative voltages and a second, minor fluorescence component at more depolarized voltages, in a similar voltage range as gate opening (Fig.…”
Section: Kcne1supporting
confidence: 54%
“…We showed in other studies that KCNE1 shifts a component of the S4 movement of KCNQ1 to more negative voltages relative to that of KCNQ1 alone (although to a lesser extent than KCNE3) (Fig. 1D, red triangles), but shifts the gate opening to more positive voltages (29,30) (Fig. 1D, black triangles).…”
Section: Significancementioning
confidence: 51%
See 1 more Smart Citation